2009
DOI: 10.1111/j.1476-5381.2008.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan induces NO production through p38 MAPK, ERK and Akt in porcine coronary endothelial cells: role for mitochondrial KATPchannel

Abstract: Background and purpose: Levosimendan acts as a vasodilator through the opening of ATP-sensitive K + channels (KATP) channels. Moreover, the coronary vasodilatation caused by levosimendan in anaesthetized pigs has recently been found to be abolished by the nitric oxide synthase (NOS) inhibitor N w -nitro-L-arginine methyl ester, indicating that nitric oxide (NO) has a role in the vascular effects of levosimendan. However, the intracellular pathway leading to NO production caused by levosimendan has not yet been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 55 publications
6
69
0
3
Order By: Relevance
“…In very good agreement with our data, other investigators found that levosimendan and its metabolite OR-1896 elicit a substantial vasodilation and an increase in nitric oxide production in the coronary and skeletal muscle arterioles by activating voltage-sensitive, calcium-activated and ATPsensitive potassium channels. [29][30][31] This response to levosimendan could partly be prevented by the K(ATP) channel blockers. [29][30][31] Moreover, in an in vivo rat model of coronary ischemia-reperfusion, levosimendan decreased infarct size markedly through the K(ATP) channel-dependent pathway, whereas the PDE-III inhibitor enoximone did not cause any infarct size reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In very good agreement with our data, other investigators found that levosimendan and its metabolite OR-1896 elicit a substantial vasodilation and an increase in nitric oxide production in the coronary and skeletal muscle arterioles by activating voltage-sensitive, calcium-activated and ATPsensitive potassium channels. [29][30][31] This response to levosimendan could partly be prevented by the K(ATP) channel blockers. [29][30][31] Moreover, in an in vivo rat model of coronary ischemia-reperfusion, levosimendan decreased infarct size markedly through the K(ATP) channel-dependent pathway, whereas the PDE-III inhibitor enoximone did not cause any infarct size reduction.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] This response to levosimendan could partly be prevented by the K(ATP) channel blockers. [29][30][31] Moreover, in an in vivo rat model of coronary ischemia-reperfusion, levosimendan decreased infarct size markedly through the K(ATP) channel-dependent pathway, whereas the PDE-III inhibitor enoximone did not cause any infarct size reduction. 32 Thus, the role of PDE inhibition as a mediator of the beneficial effects of levosimendan found in this study remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A -kardiológiai alkalmazása kapcsán inodilatátor hatású szerként ismert -levosimendan a klasszikus kémi-ai kondicionálószerek közé tartozik. Fő hatása -RISKaktivátor [28] és NO-felszabadító [29] hatása melletta mitokondriális K + ATP -csatorna nyitása, amely a mitokondrium integritásának, illetve a terminális oxidá-ció pontos működésének megőrzéséhez vezet [30]. Ebbéli antiischaemiás, gyulladásgátló hatása saját kísér-letünkben is igazolódott, ahol a "korai" (1-3 órás), illetve "késői" (24 órás) preoperatív előkezelés a máj I-R károsodásának csökkenéséhez vezetett.…”
Section: Kondicionáló Eljárások éS Máj Ischaemiareperfúzió -áLlatkíséunclassified
“…Experiments were performed in primary culture cells, PCAEC, which were isolated from coronary arteries of anaesthetized pigs, as described previously (Grossini et al 2009). The cells were plated into 0.1% gelatincoated culture dish by endothelial growth media-2 (EGM-2; EGM-2 BulletKit (CC-3124); Lonza, Inc., Basel, Switzerland) with the addition of human epidermal growth factor, hydrocortisone, gentamycin-amphotericin-B 1000, 2% foetal bovine serum (FBS), vascular endothelial growth factor, human fibroblast growth factor-basic, recombinant analogue insulin-like growth factor 1-human, ascorbic acid, heparin (Lonza) and 1% penicillin-streptomycin-glutamine (Sigma-Aldrich) and maintained in incubator at 37 8C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%